MANTEGAZZA E GLI STUDENTI UNIVERSITARI NEGLI ANNI â€™89-â€™95 (Istituto Lombardo - Accademia di Scienze e Lettere • Incontri di Studio, 2018)
With his report, Mons. Francesco Giovanni Brugnaro, Archbishop of Camerino - San Severino Marche, offers a personal testimony of his experience as a priest, friend and colleague of the Rectoral Prof. Paolo Mantegazza, who he met in the years ‘89-’95 during his chaplain service at the Rectory of Santa Maria Annunciata of the University of Milan. In addition to the affectionate and grateful remembrance towards the exemplary role of rector, father and teacher, he adds some characteristics regarding the relationship that Prof. Mantegazza knew to weave with the university students, careful to consider the person as a whole rather than as a subject impersonal and anonymous. This special attention stemmed from the profound conviction that education is much more than simple teaching. He introduced in his long experience as a teacher the one that transformed his courses into real schools of life: the human and ethical contribution to face the most difficult future challenges in the professional field. For this reason he was also a great mediator for the very talented teachers to keep the relationship between scientific and didactic research high, between the quality of the preparation for the doctorate-specialization and the moral and methodological seriousness of the future professional. In the memory of Mons. Brugnaro, the pain that struck the Mantegazza family for the tragic and premature disappearance of the two beloved sons is preserved. Inspired also by Don Giussani’s charism, together with his wife Andreina, he was able to transform that lacerating pain into an exemplary witness of Christian life founded on the Resurrection of Christ. The common attendance of the Archbishop of Milan from 1979 to 2002, allowed both to live a daily faith, drawn from the prophetic vision of the biblical pastoral of Card. Martini also within the University, stimulating the chair of non-believers.